Land Tenure and Credit - a Study in Selected Areas of Mymensingh - Haque, Z; Jinan, T (Journal of Environmental Science and Natural Resources, 2018)
The present study aims at investigating into the existing land tenure system and its relationship with credit at Trishal Upazila of Mymensingh district. Keeping in view the objectives, 70 samples were randomly selected. The respondents have taken loan from institutional, semi institutional and non-institutional sources of credit for producing crops. The study reveals that the absentee land owner and part operator in the area have got more access to institutional sources of credit because of their ability to offer land as security. Tenants on the other hand were found to have no loan at all from the BKB because of their inability to offer collateral against loan. The tenant farmers however, were found to have access to semi institutional sources like GB and BRAC. The respondents therefore, need not be so dependent at present on money lenders and non-institutional sources of credit because of institutional and semi-institutional network present close to the study area. A lion’s share of loaned money obtained has been productively utilized by the sampled respondents irrespective of tenure categories implying the borrower’s positive attitudes towards productive utilization. J. Environ. Sci. & Natural Resources, 10(2): 143-150 2017